Decreased frequency and duration of tooth brushing is a risk factor for endothelial dysfunction. (15th August 2017) - Matsui, Shogo; Kajikawa, Masato; Maruhashi, Tatsuya; Iwamoto, Yumiko; Iwamoto, Akimichi; Oda, Nozomu; Kishimoto, Shinji; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; Goto, Chikara; Aibara, Yoshiki; et al.
Abstract: Background: Periodontal disease is associated with endothelial dysfunction, leading to cardiovascular disease. The effect of detailed tooth brushing behavior, not only frequency but also duration of tooth brushing, on endothelial function is unclear. The purpose of this study was to evaluate the relationships of detailed methods of tooth brushing with vascular function. Methods: We evaluated flow-mediated vasodilation (FMD), nitroglycerine-induced vasodilation, and frequency and duration of tooth brushing in 896 subjects. We divided the subjects into three groups according to the frequency and duration of tooth brushing: low frequency and short duration group (< twice/day and < 2 min/procedure), low frequency or short duration group (< twice/day or < 2 min/procedure), non-low frequency and non-short duration group (≥ twice/day and ≥ 2 min/procedure). Results: FMD in the low frequency and short duration group was significantly lower than FMD in the low frequency or short duration group and FMD in the non-low frequency and non-short duration group [3.1 (2.7)% vs. 4.2 (3.1)% and 4.7 (3.1)%, P  = 0.001 and < 0.001, respectively]. Nitroglycerine-induced vasodilation was similar in the three groups. Using the non-low frequency and non-short duration group as the reference, the low frequency and short duration of tooth brushing group was significantly associated with an increased odds ratio of a low FMD tertile after adjustment for conventional risk factors (OR: 2.25, 95% CI: 1.39–3.59; P  < 0.001). Conclusions: These findings suggest that low frequency and short duration of tooth brushing are associated with endothelial dysfunction. Clinical trial registration information : URL for clinical trial:http://UMIN ; registration number for clinical trial: UMIN000003409.